Pre-end-stage renal disease visit-to-visit systolic blood pressure variability and post-end-stage renal disease mortality in incident dialysis patients. Issue 9 (September 2017) - Sumida, Keiichi; Molnar, Miklos Z.; Potukuchi, Praveen K.; Thomas, Fridtjof; Lu, Jun Ling; Yamagata, Kunihiro; Kalantar-Zadeh, Kamyar; Kovesdy, Csaba P.
Abstract : Objectives: Higher SBP visit-to-visit variability (SBPV) has been associated with increased risk of adverse events in patients with chronic kidney disease, but the association of SBPV in advanced nondialysis-dependent chronic kidney disease with mortality after the transition to end-stage renal disease (ESRD) remains unknown. Methods: Among 17 729 US veterans transitioning to dialysis between October 2007 and September 2011, we assessed SBPV calculated from the SD of at least three intraindividual outpatient SBP values during the last year prior to dialysis transition (prelude period). Outcomes included factors associated with higher prelude SBPV and post-transition all-cause, cardiovascular, and infection-related mortality, assessed using multivariable linear regression and Cox and competing risk regressions, respectively, adjusted for demographics, comorbidities, medications, cardiovascular medication adherence, SBP, BMI, estimated glomerular filtration rate, and type of vascular access. Results: Modifiable clinical factors associated with higher prelude SBPV included higher SBP, use of antihypertensive medications and erythropoiesis-stimulating agents, inadequate cardiovascular medication adherence, and catheter use. After multivariable adjustment, higher prelude SBPV was significantly associated with higher post-ESRD all-cause and infection-related mortality, but not cardiovascular mortality [hazard/subhazard ratios (95% confidence interval) for the highest (vs. lowest) quartile of SBPV, 1.08 (1.01–1.16), 1.02 (0.89–1.15), and 1.41 (1.10–1.80) for all-cause, cardiovascular, and infection-related mortality, respectively]. Conclusion: High pre-ESRD SBPV is potentially modifiable and associated with higher all-cause and infection-related mortality following dialysis initiation. Further studies are needed to test whether modification of pre-ESRD SBPV can improve clinical outcomes in incident ESRD patients. Video abstract: http://links.lww.com/HJH/A772 Abstract : Supplemental Digital Content is available in the text